Methacrylamide-modified collagen hydrogel with improved anti-actin-mediated matrix contraction behavior. Issue 45 (1st November 2018) - Yang, Ke; Sun, Jing; Guo, Zhenzhen; Yang, Jirong; Wei, Dan; Tan, Yanfei; Guo, Likun; Luo, Hongrong; Fan, Hongsong; Zhang, Xingdong
Abstract : A collagen-based chondro-inductive hydrogel with improved mechanical properties was developed to promote chondrogenesis of BMSCs by resisting actin-mediated matrix contraction. Abstract : For an ideal biomimetic microenvironment to realize reliable cartilage regeneration, the ability to induce mesenchymal stem cell (MSCs) differentiation along the chondrogenic lineage and prevent further dedifferentiation is expected. With native bioactivity, collagen has been proved to be preferential for inducing the chondrogenic differentiation of MSCs. However, the phenotypic maintenance of differentiated chondrocytes in a collagen matrix is still a challenge. Actin traction, which causes drastic contraction of the collagen matrix, is frequently observed and might be an important factor that affects cell fates including chondrogenic differentiation and phenotypic maintenance. In this study, photochemical modification was applied to acquire collagen hydrogels with improved mechanical strength and creep behavior. Accompanied by inherited bioactivity, the photo-crosslinked collagen hydrogel well supported the actin cytoskeleton functionalization while resisting the actin-mediated matrix contraction. Benefitting from this, the hydrogel system promoted MSCs proliferation and chondrogenic differentiation, and more importantly, prevented further dedifferentiation. By exploring the mesenchymal development-related signal transduction markers, it was revealed that the promoted chondrogenesis was achieved through inhibiting the over-expression of MAPK and Wnt/β-catenin signaling pathways that up-regulated dedifferentiated gene expression. The strategy of applying the hydrogel system to cartilage regeneration is foreseeable based on the positive heterotopic and orthotopic chondrogenic differentiation.